Organic Cocrystals: Recent Advances and Perspectives for Electronic and Magnetic Applications - Jiang, Mengjia; Zhen, Chun; Li, Shuyu; Zhang, Xiaotao; Hu, Wenping (Frontiers in Chemistry, 2021)
Cocrystals engineering is an advanced supramolecular strategy that has been attracting extensive works for research. Many reports toward cocrystals in different application fields come into our sight, especially focusing on the field of photonics. However, there are few articles combining and summing up the electronic and magnetic properties of cocrystals. In this review, we firstly introduce the growth methods that are the basis for realizing the different characteristics of cocrystals. Then we present an overview of applications of cocrystals in electronic and magnetic fields. Some functional devices made of cocrystals are also introduced. We hope this review can provide researchers and students with a more comprehensive understanding of the latest development, progress, and prospect of cocrystals.